Strategic foundations of general equilibrium dynamic matching and bargaining games - Gale, Douglas 1950- (Cambridge University Press, 2000)
The theory of competition has held a central place in economic analysis since Adam Smith. This book, written by one of the most distinguished of contemporary economic theorists, reports on a major research program to provide strategic foundations for the theory of perfect competition. Beginning with a concise survey of how the theory of competition has evolved, Gale makes extensive and rigorous use of dynamic matching and bargaining models to provide a more complete description of how a competitive equlibrium is achieved. Whereas economists have made use of a macroscopic description of markets in which certain behavioral characteristics, such as price-taking behavior, are taken for granted, Gale uses game theory to re-evaluate this assumption, beginning with individual agents and modelling their strategic interaction. A strategic foundation for competitive equilibrium shows how such interaction leads to competitive, price-taking behavior. Essential reading for graduate courses in game theory and general equilibrium
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Competition; Equilibrium (Economics); Game theory; Spieltheorie; Gleichgewichtstheorie; Wettbewerbstheorie